FERTILITY AND MORTALITY REGISTRATION IN IRAN - H. Razmara (Tehran University of Medical Sciences, 1971)
Record registration was initiated in 1918 in Iran, but the office of the registration and identity card began with the law passed in 1925. From 1939 taking census started in the cities and until September 1941 census was taken in 35 cities. The first national census was taken in 1956. In 1958, the department of statistics was separated from that office and began its work as the general office for the public statistics, the remainder of the office continued as the general office of the record registration. The latter has 157 regional offices, each with central branches and several static units (Nationally 361) and some mobile or village units (755). Their work is to register birth and death. Existing problems in registration and the future objective work project, to be initiated, have been discussed and suggestions to omit the present deficiencies have been made.